The effect of cyberchondria on anxiety, depression and quality of life during COVID-19: the mediational role of obsessive-compulsive symptoms and Internet addiction - Federica Ambrosini; Roberto Truzoli; Matteo Vismara; Daniele Vitella; Roberta Biolcati (Heliyon, 2022)
Since the global pandemic of the coronavirus disease 2019 (COVID-19), online health information-seeking behaviors have notably increased. Cyberchondria can be a vulnerability factor for the worsening of anxiety-depressive symptoms and quality of life. The current study aims to understand the predictive effect of cyberchondria on health anxiety, anxiety, depression and quality of life considering the mediating effect of obsessive-compulsive symptoms and Internet addiction and the moderating effect of COVID anxiety. 572 Italian participants (66% female; Mean age = 34; SD = 15) took part in a cross-sectional online survey involving CSS-12, MOCQ-R, IAT, SHAI, HADS, WHOQoL-BREF and CAS. Mediation and moderation analyses were conducted. Obsessive-compulsive symptoms and Internet addiction were found to partially mediate the cyberchondria-health anxiety and the cyberchondria-anxiety links and to totally mediate the cyberchondria-depression and the cyberchondria-quality of life links. COVID anxiety was found to moderate the relationship between cyberchondria and anxiety. The findings suggest that compulsivity may have a key role in the explanation of the underlying mechanisms of cyberchondria. Healthcare practitioners should provide additional support for individuals with cyberchondria. As such, cyberchondria is a contributing factor to the exacerbation of anxiety-depressive disorders and may impact on the quality of life.